Resposta :
O Produto da Soma pela Diferença de Dois Termos
É dado por :
O quadrado do primeiro termo menos o quadrado do segundo termo.
- (x + a)(x - a)= x² - a²
(x + 3) . (x – 3) =
= x² - 3²
= x² - 9
(2x + 3y) . (2x – 3y) =
= (2x)² - (3y)²
= 4x² - 9y²
(4x + 2y) . (4x – 2y) =
= (4x)² - (2y)²
= 16x² - 4y²
(6a + 8) . (6a – 8) =
= (6a)² - 8²
= - 36a² - 64
◇AnnahLaryssa◇

Explicação passo-a-passo:
(x + 3) . (x – 3)
x²-3²
x²-9
(2x + 3y) . (2x – 3y)
(2x)²-(3y)²
4x²-9y²
(4x + 2y) . (4x – 2y)
(4x)²-(2y)²
16x²-4y²
(6a + 8) . (6a – 8)
(6a)²-(8)²
36a²-64